2012
DOI: 10.1155/2012/510291
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Stress Reduction Programs upon Ambulatory Blood Pressure among African American Adolescents: Influences of Endothelin-1 Gene and Chronic Stress Exposure

Abstract: Stress-activated gene × environment interactions may contribute to individual variability in blood pressure reductions from behavioral interventions. We investigated effects of endothelin-1 (ET-1) LYS198ASN SNP and discriminatory stress exposure upon impact of 12-week behavioral interventions upon ambulatory BP (ABP) among 162 prehypertensive African American adolescents. Following genotyping, completion of questionnaire battery, and 24-hour ABP monitoring, participants were randomized to health education cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…We have observed promising results from two 3-month smartphone delivered TT trials (37,41,42), where TT was found to be highly acceptable and intuitive in its use. In addition, clinically meaningful reductions in resting BP, ambulatory BP and reductions in SNS activation (i.e., reduced morning awakening curve of salivary alpha amylase) have been observed in preEH White and African American adults outlining a biological mechanistic pathway for BAM and resultant stress reduction (15,41,42).…”
Section: Background Of Ttmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed promising results from two 3-month smartphone delivered TT trials (37,41,42), where TT was found to be highly acceptable and intuitive in its use. In addition, clinically meaningful reductions in resting BP, ambulatory BP and reductions in SNS activation (i.e., reduced morning awakening curve of salivary alpha amylase) have been observed in preEH White and African American adults outlining a biological mechanistic pathway for BAM and resultant stress reduction (15,41,42).…”
Section: Background Of Ttmentioning
confidence: 99%
“…Stress exposure also increases unhealthy coping behaviors such as comfort eating, smoking, excessive alcohol intake, pharmaceutical abuse and increased sedentary activity. These behaviors exacerbate psychological and physiological stress-related symptoms and increase risk for disease (9)(10)(11)(12)(13)(14)(15). There is reason to believe health disparities also contribute to stress resulting in differences in trust and engagement in the health care system (16).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have examined and demonstrated that stress-related gene · environment contributions can modulate the benefit of a meditation intervention in terms of ambulatory blood pressure reduction. 5 Another potential modulator that we have not fully examined is adherence.…”
mentioning
confidence: 99%
“…Its widespread potential effects include modification of risk for HTN in the overweight/obese population (41-43), BP reactivity to stressors (44)(45)(46), idiopathic pulmonary arterial Figure 4. Comparison in European descent subjects and African descent subjects of aldosterone/renin ratio was obtained on a restricted salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…Several other factors may, in part, explain the differences between the AD and ED. First, some studies have reported a relationship between the level of stress and the relationship between BP and EDN1 polymorphism and between AD and BP (45,46,55,56). Stress profiles are not present in the HyperPATH data set, and salt sensitivity of BP, ALDO, ARR, or SASSI-II were not performed in these previous studies.…”
Section: Figure 5 Comparison In European Descent Subjects and Africamentioning
confidence: 99%